2021
DOI: 10.3390/antiox10050696
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Transplantation Modulates Inflammation and Apoptosis, Alleviating Tendinopathy Both In Vivo and In Vitro

Abstract: Tendinopathy is a common musculoskeletal condition causing pain and dysfunction. Conventional treatment and surgical procedures for tendinopathy are insufficient; accordingly, recent research has focused on tendon-healing regenerative approaches. Tendon injuries usually occur in the hypoxic critical zone, characterized by increased oxidative stress and mitochondrial dysfunction; thus, exogenous intact mitochondria may be therapeutic. We aimed to assess whether mitochondrial transplantation could induce anti-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 63 publications
3
39
0
Order By: Relevance
“…The authors concluded that mitochondrial protection might protect tendon and promote tendon healing. Subsequently in the same year, one research group transplanted exogeneous intact mitochondria isolated from mesenchymal stromal cells derived from umbilical cord (UC-MSCs) to TNF-α-treated tenocytes and successfully attenuated oxidative stress, promoted mitochondrial functional recovery, restored the expression of tenogenic markers, inhibited apoptosis, and reduced the expression of pro-inflammatory markers and pNF-kB in damaged tenocytes [ 115 ]. Similarly, local injection of mitochondria isolated from L6 myoblasts to the Achilles tendon 2 weeks after collagenase-induced injury reduced the expression of apoptosis and pro-inflammatory markers, pNF-kB, MMP1 and increased collagen content 2 weeks after injection [ 115 ].…”
Section: Anti-oxidative Therapies For the Promotion Of Tendon Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that mitochondrial protection might protect tendon and promote tendon healing. Subsequently in the same year, one research group transplanted exogeneous intact mitochondria isolated from mesenchymal stromal cells derived from umbilical cord (UC-MSCs) to TNF-α-treated tenocytes and successfully attenuated oxidative stress, promoted mitochondrial functional recovery, restored the expression of tenogenic markers, inhibited apoptosis, and reduced the expression of pro-inflammatory markers and pNF-kB in damaged tenocytes [ 115 ]. Similarly, local injection of mitochondria isolated from L6 myoblasts to the Achilles tendon 2 weeks after collagenase-induced injury reduced the expression of apoptosis and pro-inflammatory markers, pNF-kB, MMP1 and increased collagen content 2 weeks after injection [ 115 ].…”
Section: Anti-oxidative Therapies For the Promotion Of Tendon Repairmentioning
confidence: 99%
“…Subsequently in the same year, one research group transplanted exogeneous intact mitochondria isolated from mesenchymal stromal cells derived from umbilical cord (UC-MSCs) to TNF-α-treated tenocytes and successfully attenuated oxidative stress, promoted mitochondrial functional recovery, restored the expression of tenogenic markers, inhibited apoptosis, and reduced the expression of pro-inflammatory markers and pNF-kB in damaged tenocytes [ 115 ]. Similarly, local injection of mitochondria isolated from L6 myoblasts to the Achilles tendon 2 weeks after collagenase-induced injury reduced the expression of apoptosis and pro-inflammatory markers, pNF-kB, MMP1 and increased collagen content 2 weeks after injection [ 115 ]. Pretreatment of Achilles tenocytes with Alda-1, a selective activator of mitochondrial aldehyde dehydrogenase 2 (ALDH2), which alleviates oxidative stress and ER stress, attenuated H 2 O 2 -induced cell death, oxidative stress, mitochondrial membrane depolarization and apoptosis [ 23 ].…”
Section: Anti-oxidative Therapies For the Promotion Of Tendon Repairmentioning
confidence: 99%
“…[62] Total protein measurement has been performed by bicinchoninic acid assay (BCA), Bradford, Biuret, and Lowry methods. Lee et al [30] determined the amount of isolated mitochondrial protein using the BCA method in the tendinopathy model. Huang et al [28] demonstrated that the total amount of mitochondrial protein was determined by the Bradford method on the brain ischemia model.…”
Section: Tissue-cell Sources and Isolation Process For Mitochondrial Transplantationmentioning
confidence: 99%
“…[28] Similarly, Sun et al [36] transplanted 750 and 1500 µg mitochondria on the acute respiratory distress syndrome model. Lee et al [30] injected 10 and 50 µg mitochondria into the Achilles tendon on the tendinopathy model, and Zhou et al [43] injected 0.2 or 0.4 mg/kg mitochondria once every day for 7 days…”
Section: Doses Of Mitochondrial Transplantationmentioning
confidence: 99%
“…Hence, exploring a novel strategy that effectively counteracts inflammation-induced secondary injuries is critical for treating traumatic SCI. Recently, a mitochondria-targeted treatment has emerged as a potential anti-inflammatory intervention ( Wang et al, 2019 ; Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%